The personal and professional characteristics and perspectives of secondary school principals in the National Capital Region of the Philippines - Samia, Elizabeth Salvador (1989)
The purpose of the study was to describe and analyze the personal and professional characteristics and perspectives of secondary school principals from the National Capital Region of the Philippines. A questionnaire, adapted from the 1987 National Association of Secondary School Principals' study on high school leaders in the US, was sent to a sample of 167 principals in NCR. The research revealed that the secondary school principals in NCR were mostly females in their 50's or 60's. Most of them had master's degrees in education and had more than 10 years of teaching experience as well as administrative experience. They were involved in various professional activities and were members of at least one professional educational organization.
Thesis (Ph.D. Education)--University of South Carolina.
Keywords: High school principals -- Philippines -- Manila metropolitan area